Bridges - Wouter Zant (Tinbergen Institute, 2017)
We estimate to what extent bridges in Mozambique lead to transport cost reductions and attribute these reductions to key determinants, in particular road distance, road quality and crossing borders. For identification we exploit the introduction of a road bridge over the Zambezi river, in August 2009 between Caia and Chimuara, with the simultaneously completed rehabilitation of the railway bridge between Vila de Sena and Mutarara, which jointly create variation in optimal trading itineraries between markets. Estimations, based on monthly maize prices in 24 markets, for up to five years before and after the (re)introduction of the bridges, are conditioned on spatial price equilibrium with market integration. Bridges explain a reduction of transport costs, averaged over itineraries, from 17% to 42% (ATT). Results are shown to be robust for the non-random bridge placement and various other threats. Reduction in transport costs for particular itineraries is occasionally even larger, and is, generally, mainly due to road distance and modestly to road quality.
Keywords: D23; D61; O13; O18; Q13; R41; 330; agricultural markets; transport costs; bridges; Mozambique; sub-Sahara Africa